1971
DOI: 10.1111/j.1476-5381.1971.tb07074.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cardiac glycosides studied in the isolated perfused guinea‐pig liver

Abstract: Summary1. Metabolic degradation of tritiated ouabain, digoxin, and digitoxin has been investigated quantitatively using the isolated perfused guinea-pig liver. The cardiac glycosides and their metabolites have been extracted from the plasma, liver, and bile by different solvents and identified as far as possible by radiochromatographic analysis.2. The total metabolic activity in the experimental system was localized in the liver.3. The hydrophilic glycoside ouabain could not penetrate into the metabolically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…This implies a lesser desired effect as gallic acid is metabolized in vivo. The same was done for the cardiac glycosides, with the cardenolide moiety as a representative ligand (Kolenda et al 1971;Rietbrock et al 1977). In contrast, the most favorable binding pose (Fullfitness: − 38,028.785 kcal/mol) of the cardenolide moiety interacted with Aβ 1-42 in the latter part of the first ten residues, particularly with Hsp6 (protonated His) and Tyr10 via hydrophobic interactions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This implies a lesser desired effect as gallic acid is metabolized in vivo. The same was done for the cardiac glycosides, with the cardenolide moiety as a representative ligand (Kolenda et al 1971;Rietbrock et al 1977). In contrast, the most favorable binding pose (Fullfitness: − 38,028.785 kcal/mol) of the cardenolide moiety interacted with Aβ 1-42 in the latter part of the first ten residues, particularly with Hsp6 (protonated His) and Tyr10 via hydrophobic interactions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specially, the lipid-soluble cardiac glycosides are easily metabolized. 6 Also, the laboratory test against this toxin is uncommonly used, leading to negative toxicological analysis report for such cases. Thus, history and evidence surrounding the incident are very important in such cases to draw a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…9 is further supported by the finding that the T/M ratio of the digitalis glycosides changes throughout the perfusion: in the first 2 h it reaches a value of about 10 and subsequently decreases to approximately 3, thus indicating a continuous increase of the ratio hydrophilic metabolites/lipophilic glycosides in the plasma. The polar metabolites found in the plasma must have been redistributed from the liver into the blood since it has been shown that a conversion of these glycosides does not occur in the blood itself (Kolenda et al, 1971 ;Liullmann et al, 1969). The newly appearing metabolites are distributed between plasma and liver in the same way as ouabain ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The polar metabolites found in the plasma must have been redistributed from the liver into the blood since it has been shown that a conversion of these glycosides does not occur in the blood itself (Kolenda et al, 1971 ;Liullmann et al, 1969). The newly appearing metabolites are distributed between plasma and liver in the same way as ouabain (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation